2011
DOI: 10.2146/ajhp100309
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol for the treatment of heart failure

Abstract: PURPOSE. The pharmacology, pharmacokinetics, efficacy, safety, and place in therapy of nebivolol are reviewed. SUMMARY. Nebivolol, a third-generation, highly β(1)-specific β-blocker, is labeled for the treatment of hypertension in the United States. In addition to its β-blocking effects, nebivolol has been shown to increase endothelin-dependent nitric oxide, giving it a unique peripheral vasodilatory action. Nebivolol is extensively metabolized by cytochrome P-450 isoenzyme 2D6. In patients with heart failure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…However, at the present time, only few studies have examined the role of cardiac β 1 - and β 2 -adrenoceptor (β-AR) subtypes in the pathogenesis of Dox-cardiotoxicity [9], [10] and only one study, at late-onset Dox-CM, assessed β 3 -AR subtype [11], which is recently described as a new target for some β-blockers such as nebivolol [12], [13]. Despite this lack in experimental data, some clinical studies investigated β-blocker therapies in Dox-CM.…”
Section: Introductionmentioning
confidence: 99%
“…However, at the present time, only few studies have examined the role of cardiac β 1 - and β 2 -adrenoceptor (β-AR) subtypes in the pathogenesis of Dox-cardiotoxicity [9], [10] and only one study, at late-onset Dox-CM, assessed β 3 -AR subtype [11], which is recently described as a new target for some β-blockers such as nebivolol [12], [13]. Despite this lack in experimental data, some clinical studies investigated β-blocker therapies in Dox-CM.…”
Section: Introductionmentioning
confidence: 99%
“…This synthesis is catalyzed by an enzyme known as nitric oxide synthase. 14 There are three isoforms of this enzyme namely endothelial nitric oxide synthase (found in the cardiomyocytes and endothelial cells), neuronal nitric oxide synthase (found in the brain), and inducible nitric oxide synthase (found in macrophages). In this pathway, nitric oxide synthase cleaves the nitrogen from the guanidino group of arginine and subsequently form citrulline and NO.…”
Section: Dynamic Roles Of Nitric Oxide and Nebivolol As Its Potentiatormentioning
confidence: 99%
“…The production of nitric oxide by the NO synthase present in the endothelium is enhanced. 14,16 Moreover, in a study by Gauthier et al it was found that beta-3 adrenoreceptors are also present and functional in the heart and were responsible for the unexpected negative inotropic effects of epinephrine, norepinephrine, and was important in the pathophysiology of heart diseases and indeed, beta-3 receptors found to be important in the pathophysiology of different cardiovascular diseases including heart failure. 17 The effects of nebivolol actions on the heart are mediated via beta-3 receptors to release nitric oxide.…”
Section: Dynamic Roles Of Nitric Oxide and Nebivolol As Its Potentiatormentioning
confidence: 99%
“…Nevertheless, in oral drug delivery there is a need for innovative drug delivery systems due to low drug solubility, poor gastrointestinal absorption, metabolism related variability issues, continuous fluctuation of drug plasma levels and food effects [7,8]. Nebivolol is absorbed rapidly after oral administration and is not affected by food; however, it has variable absolute oral bioavailability due to its extensive first-pass metabolism [9]. Due to the low aqueous solubility and high membrane permeability, NBV is categorized as a Class II drug according to Biopharmaceutics Classification System [10].…”
Section: Introductionmentioning
confidence: 99%